Implementing CSR to Strengthen Corporate Image: The Strategy of PT Telkom Indonesia Witel Solo - Anisa Febri Tri Wahyuni; Rona Rizkhy Bunga Chasana (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Social responsibility has become something that companies must implement. Companies are legally required to fulfill their social responsibility obligations toward the environment and society. PT Telkom Indonesia Witel Solo carries out corporate social responsibility activities, one of which is planting mangrove trees to prevent coastal erosion and support the achievement of the Sustainable Development Goals (SDGs). In addition to complying with existing regulations, the company receives feedback from its stakeholders in the form of image or reputation through a strategy that emerges from CSR activities. Stakeholder involvement in the implementation of CSR is something that the company needs to pay attention to. This research aims to identify the corporate social responsibility (CSR) strategy employed by PT Telkom Indonesia Witel Solo to enhance its image. This study uses qualitative methods with data analysis according to Miles and Huberman to obtain results that aligned with the research objectives. The findings show that the company implements active participation strategies with its stakeholders, adheres to business ethics, establishes communication and maintains sustainable relationships, and creates value through social and environmental programs in the implementation of profit, people, and planet.